Orogenesis without collision: Stabilizing the Terra Australis accretionary orogen, eastern Australia - Cawood, P.; Leitch, E.; Merle, R.; Nemchin, Alexander (Geological Society of America, 2011)
The Neoproterozoic to end-Paleozoic Terra Australis orogen extended along the Gondwana margin of the paleo–Pacifi c Ocean, and it now provides a detailed record of orogenic activity and continental stabilization within an ongoing convergent, accretionary plate margin. New geochronological data from end-Paleozoic plutonic and volcanic rocks associated with the Gondwanide orogeny in the New England region of eastern Australia, integrated with information on the nature and timing of associated sedimentation, deformation, and metamorphism, allow resolution of a high-fidelity record of orogenesis. At the end of the Carboniferous, around 305 Ma, convergent margin magmatism, which had been active along the western margin of the New England region, terminated and was followed by a short pulse of regional compressional deformation and metamorphism, marking the commencement of the Tablelands phase of Gondwanide orogenesis. Deformation was almost immediately followed by the onset of clastic sedimentation and local calc-alkaline volcanism, dated at 293 Ma, in the extensional Barnard Basin. Emplacement of the two New England S-type granitic suites, the Bundarra and the Hillgrove suites, along with localized high-temperature, low-pressure metamorphism, was essentially contemporaneous, ranging in age from 296 to 288 Ma, and overlapped in time with I-type magmatism and the switch from regional compression to extension and Barnard Basin rifting.The Hunter-Bowen phase of the Gondwanide orogeny commenced with contractional deformation, resulting in termination of sedimentation in the Barnard Basin and regional deformation and metamorphism across New England and into the Sydney and Gunnedah basins to the west at around 265–260 Ma. Contractional loading of the Sydney and Gunnedah basins resulted in their conversion from extensional to foreland basins, which received ongoing pulses of sediment from the New England orogenic welt until 230 Ma. The Hunter-Bowen phase was associated with widespread I-type plutonism and volcanic activity in New England that ceased around 230 Ma, marking the termination of Gondwanide orogenesis. Orogenesis occurred in an evolving convergent plate-margin setting. S- and I-type magmatic activity ranging in age from ca. 300 to 230 Ma represents a stepping out of arc magmatism from the western margin of New England (prior to 305 Ma) into the preexisting arc-trench gap. There is no evidence that deformation was related to the collision of the convergent margin with a major lithospheric mass, and the widespread development of extensional basins in the eastern third of Australia in the Early Permian indicates control by phenomena acting on a continental scale, probably changing plate kinematics associated with the amalgamation of Pangea.